1981
DOI: 10.1007/bf00386544
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of a hemagglutinin associated with cell walls from hypocotyls of Vigna radiata

Abstract: The hemagglutinin (lectin) associated with the cell walls of hypocotyls from Vigna radiata was greatly purified. At every stage in the purification the hemagglutinating activity coincided exactly with α-galactosidase activity. This suggests that, similar to the seed lectin of the same plant, both activities might be present in the same molecule which has a molecular weight of about 170,000. When the purification was performed in the absence of d-galactose and 2-mercaptoethanol (method A), the native molecule a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The first record on Leguminosae lectin localization on protein bodies was reported in 1975 (Clarke et al, 1975); however, this study did not use immunocytochemistry as a supporting assay. Since then, some studies have reported on lectin localization in D. lehmanni (Melgarejo and Pérez, 1997), Glycine max (Horisberger and Vonlanthen, 1980), Vigna radiata cell walls (Haab et al, 1981), Phaseolus vulgaris (Manen and Pusztai, 1982), Canavalia ensiformis (Herman and Shannon, 1984) and C. mollis (Santos et al, 2004). These studies revealed the presence of lectin in storage parenchymatic cells, specialized vacuoles termed protein bodies, cytoplasm or cell wall.…”
Section: Cotyledon Cell Ultrastructure and Lectin Immunolocalizationmentioning
confidence: 99%
“…The first record on Leguminosae lectin localization on protein bodies was reported in 1975 (Clarke et al, 1975); however, this study did not use immunocytochemistry as a supporting assay. Since then, some studies have reported on lectin localization in D. lehmanni (Melgarejo and Pérez, 1997), Glycine max (Horisberger and Vonlanthen, 1980), Vigna radiata cell walls (Haab et al, 1981), Phaseolus vulgaris (Manen and Pusztai, 1982), Canavalia ensiformis (Herman and Shannon, 1984) and C. mollis (Santos et al, 2004). These studies revealed the presence of lectin in storage parenchymatic cells, specialized vacuoles termed protein bodies, cytoplasm or cell wall.…”
Section: Cotyledon Cell Ultrastructure and Lectin Immunolocalizationmentioning
confidence: 99%